Reducing the Spatial Discretization Error of Thermal Emission in Implicit Monte Carlo Simulations. Issue 1 (23rd February 2016) - Irvine, Adam Glenn; Boyd, Iain D.; Gentile, Nicholas A.
Abstract : Implicit Monte Carlo simulations of thermal radiative transport can exhibit what is known as teleportation error in problems with strong coupling between radiation and matter. Teleportation error occurs when energy deposited in a localized region of a spatial zone is emitted throughout the zone in the next time step. Teleportation error is commonly reduced by biasing the positions of photon thermal emission using a fit to the spatial distribution of temperature to the fourth power. The current work samples and stores locations along photon paths based on absorption probabilities. These locations are used as sites for emission in the subsequent time step. This method of teleportation correction is demonstrated in several sample problems, and is validated against an Implicit Monte Carlo Diffusion Method, which does not exhibit teleportation error. The new method reduces teleportation error relative to the source tilting method, and enables the use of lower spatial resolutions than would be required to mitigate teleportation error using the source tilting method.